EFISIENSI MESIN PENGERING BEKU VAKUM PADA PENGERINGAN CABAI MERAH (Capsicum annuum L.) - ., Fadarina (KINETIKA, 2020)
Vacuum freeze drying is a drying method performed at low temperature, reducing product damage caused by high temperature. Red chilies are highly perishable and seasonal, so farmers who have applied the recommended cultivation technology will produce large quantities of chilies at harvest time. This study aimed to design a vacuum freeze dryer, obtained the performance of the dryer based on the efficiency of the cooling machine, and obtained red chilies that met the water content standards based on SNI No. 01-3389-1994. The parameters measured for the cooling machine performance including time, temperature of the evaporator inlet and outlet, temperature of the condenser inlet and outlet. For red chilies drying, the measured parameters were drying temperature with variations 40oC, 45oC, 50oC, and 55oC for 13 hours. Based on the test result, the design of this vacuum freeze dryer had a maximum capacity of 6.52 L for the cold room and 3 L for the heating room. The average of the actual COP, Carnot COP, and refrigeration efficiency were 3.33, 6.18, and 53.71%respectively. The dried chilies produced met the moisture content in accordance with SNI No. 01-3389-1994, namely at temperature 50oC and 55oC with water content of 10.66% and 9.50%respectively.